The Role of Bim Technologies in the Information System of Education - Abdumutalibovich, Kokhorov Abdumonon; Lutfillaevna, Boltayeva Muhayyo (Antis Publisher, 2024)
In the article of builders professional competence increase , modern informed from technologies wide use , formation of a specialist as a well-rounded, humane, comprehensively developed person and in them competence features research done.